Bottom-up urban datafication via digital platforms: a toolkit for hybrid ethnographers - Nerea Viana Alzola (Netcom)
The literature on the digitalisation of urban life and its datafication has largely centred on top-down approaches to data production, especially within the realms of smart cities and platform urbanism. This article seeks to shift that perspective, contributing to the relatively limited body of work on bottom-up datafication, where ordinary people drive data production in today’s digital and mobile times. Specifically, it delves into how ethnographic toolkits are being reimagined to navigate this knowledge production process within the ‘hybrid city’ paradigm, where digital platforms are pervasive in everyday life.Following the ‘Ethnography’s Kitchen’ format, this study highlights both descriptive and analytical reflexivity, offering practical insights by sharing my personal toolkit. It presents four analytical tools –spatial mapping for discovery, writing for access, self-presentation for positionality, and archiving and monitoring for data collection – supported by empirical evidence drawn from fieldwork in Hamamatsu, Japan and Geneva, Switzerland.The empirical evidence emphasises the pivotal role of reflexivity in hybrid urban ethnography, particularly in grappling with the epistemological challenges posed by the digitalisation of urban life and the integration of artificial intelligence (AI) into research practices. By offering practical examples and methodological reflections, this article aspires to inspire urban ethnographers to adopt hybrid methodologies, thus fostering a deeper connection to the complexities of contemporary urban dynamics.